Come Together Now! New Technologies and Collective Representation of Platform Workers - Unterschütz, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The purpose of this short discussion paper is to outline the problems faced by collective labour law in face of new forms of work organization such as digital platforms. The digital economy has brought automation of work, digitalisation of processes and coordination by platforms. In comparison to other companies there are significant differences in the way platforms are organized and managed using algorithms. Employment platform workers have gone a long way from initial form of organising in self-help communities, guilds to co-operatives and full participation in trade union structures. Nowadays it has to be considered how to use technologies and data collected by platform companies to the benefit of workers.